AGODB: a comprehensive domain annotation database of argonaute proteins. (7th September 2022) - Li, Bowen; Yang, Shanshan; Long, Jinjin; Chen, Xue; Zhang, Qianyue; Ning, Lin; He, Bifang; Chen, Heng; Huang, Jian
Abstract: Argonaute (Ago) proteins are widely expressed in almost all organisms. Eukaryotic Ago (eAgo) proteins bind small RNA guides forming RNA-induced silencing complex that silence gene expression, and prokaryotic Ago (pAgo) proteins defend against invading nucleic acids via binding small RNAs or DNAs. pAgo proteins have shown great potential as a candidate 'scissors' for gene editing. Protein domains are fundamental units of protein structure, function and evolution; however, the domains of Ago proteins are not well annotated/curated currently. Therefore, full functional domain annotation of Ago proteins is urgently needed for researchers to understand the function and mechanism of Ago proteins. Herein, we constructed the first comprehensive domain annotation database of Ago proteins (AGODB). The database curates detailed information of 1902 Ago proteins, including 1095 eAgos and 807 pAgos. Especially for long pAgo proteins, all six domains are annotated and curated. Gene Ontology (GO) enrichment analysis revealed that Ago genes in different species were enriched in the following GO terms: biological processes (BPs), molecular function and cellular compartment. GO enrichment analysis results were integrated into AGODB, which provided insights into the BP that Ago genes may participate in. AGODB also allows users to search the database with a variety of options and download the search results. We believe that the AGODB will be a useful resource for understanding the function and domain components of Ago proteins. This database is expected to cater to the needs of scientific community dedicated to the research of Ago proteins. Database URL: http://i.uestc.edu.cn/agodb/